Pengaruh Tambahan Penghasilan Pegawai Terhadap Kinerja Aparatur Sipil Negara Di Sekretariat Daerah Kabupaten Bulukumba - Syamsul Bahri, Andi Iqra; Madani, Muhlis; Parawu, Hafiz Elfiansyah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The purpose of this study was to find out the Effect of Employee's Extra Payment on the Performance of the State Civil Apparatus at the Regional Secretariat of Bulukumba Regency which focused on the Effect of TPP on the performance of the State Civil Apparatus at the Regional Secretariat of Bulukumba Regency. This study used a quantitative research with the type of positivism philosophy research, namely to describe and explain the effect of additional employee income on the performance of the state civil apparatus in the Bulukumba district secretariat. The results of this study indicated that the regression results (influence) of Variable X on Variable Y simultaneously were only 0.319 or 31.9%, which meant that the effect of giving TPP on employee performance in the office was small. While the effect of the TPP variable (X) on performance (Y) partially showed that the results per indicator had an effect of no more than 0.227 or 22.7%, it also showed that the provision of TTP on performance at the Bulukumba Regency Secretariat was relatively small. Thus, the effect of TPP in improving performance was very small.Keywords: Influence, Performance, Employee's Extra Payment